2023
DOI: 10.1017/s0007114523001769
|View full text |Cite
|
Sign up to set email alerts
|

A systematic review of interventions targeting modifiable factors that impact dietary intake in athletes

Abstract: Appropriate dietary intake has been found to positively impact athletes’ performance, body composition, and recovery from exercise. Strategies to optimise dietary intake often involve targeting one or more of the many factors that are known to influence dietary intake. This review aims to investigate the types and effectiveness of interventions used to impact modifiable factors of dietary intake in athletes. MEDLINE, CINAHL, SPORTDiscus, and Web of Science were searched from inception to May 2022 for intervent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 63 publications
1
1
0
Order By: Relevance
“…These findings are in line with a recent systematic literature review which reported that nutrition education interventions improved nutrition knowledge in randomised controlled trials (n = 13) and single-arm pre/post-design (n = 19) studies [6]. Similar results were found in a recent systematic literature review by Janiczak et al [61], which showed all studies (10 out of 24 included) that used nutrition education interventions positively impacted nutrition knowledge, with eight of those studies having a positive impact on some aspect of dietary intake. Interestingly, we also found that nutrition education was associated with improved body contour ratings, indicating that nutrition education may have a role to play in improving body image.…”
Section: Differences In Outcome Measures Based On Socio-demographic F...supporting
confidence: 91%
“…These findings are in line with a recent systematic literature review which reported that nutrition education interventions improved nutrition knowledge in randomised controlled trials (n = 13) and single-arm pre/post-design (n = 19) studies [6]. Similar results were found in a recent systematic literature review by Janiczak et al [61], which showed all studies (10 out of 24 included) that used nutrition education interventions positively impacted nutrition knowledge, with eight of those studies having a positive impact on some aspect of dietary intake. Interestingly, we also found that nutrition education was associated with improved body contour ratings, indicating that nutrition education may have a role to play in improving body image.…”
Section: Differences In Outcome Measures Based On Socio-demographic F...supporting
confidence: 91%
“…Furthermore, traditional dietary patterns focusing on regular consumption of these products, such as the Mediterranean, Paleo, and plant-based diets, show promise; it is crucial to tailor nutritional approaches towards the unique needs of athletes, as they can vary depending on the performance level, sports discipline, and the training load (Janiczak et al, 2024). For example, the Mediterranean diet originated from the countries associated with the Mediterranean Sea, such as Italy, Greece, Spain, Morocco, Egypt, and Lebanon, and is primarily based on plants and seafood, allowing for moderate consumption of other animal proteins.…”
Section: Discussionmentioning
confidence: 99%